Influences, identity and historiography in Colombia: the reception of Brazilian modernism (1940s–1960s) - Botti, Giaime (Routledge, 2019)
The reception of Brazilian architectural modernism in Colombia has been dismissed and underestimated by national historiography. This article aims to provide a first overview of the rich system of transnational relations between Colombia and Brazil. Moving from the first acknowledgments of Brazilian architectural production in Colombia — in which triangulations with the USA played an important role, not least after the Brazil Builds exhibition catalogue reached an international audience — this article displays a varied system of transference routes that made Brazilian-Cariocan modernism one of the main references for Colombian architects during the 1950s. This text examines recognised seminal events and lesser-known facts, highlighting the existence of a wide system of connections. It analyses the reception of the work of Niemeyer and other architects in Colombian magazines and underlines the movements of Colombian architects toward Brazil. It finally recollects a varied group of projects from the 1950s that evidence the diffusion of Brazilian-Cariocan repertories in Colombia among professionals and students. The article highlights how the reception of Brazilian modernism in Colombia should be read as the result of local cases within the global process of modernism’s ‘tropicalisation’. By doing so, it also discusses the reasons that pushed this process to the margins of the mainstream historiographic narrative.